Comparing clients' satisfaction with governmental and private speechtherapy clinics of Ahvaz, Iran - Peyman Zamani (Vesnu Publications, 2013)
Introduction: Reaching ultimate therapeutic goals in rehabilitation discipline (especially, in speech therapy) requires a long-term process. Having through knowledge about the level of clients' satisfaction may, thus, be important in achieving and maintaining treatment goals. The aim of this investigation was to evaluate and compare clients' satisfaction with governmental and private speech therapy clinics offering speech therapy services in Ahvaz, Iran. Materials and Methods: In this cross-sectional comparative study, 425 subjects were randomly selected from all the clients who had attended at least 5 seasons at either governmental or private speech therapy clinics of Ahvaz city. The data was collected through face-to-face or by phone interviews and the level of participants' satisfaction was calculated based on a 0-to-100 point scale. Statistical analysis was conducted using SPSS software (version 15). Results: The mean score of clients satisfaction with private clinics (71.4 ± 0.91) was higher than those with governmental clinics (69.6 ± 5.16) and this difference was significant (P = 0.038). The satisfaction levels of private clinics' clients with the quality of physical situation of the clinic (P = 0.001), therapeutic services (P = 0.018), and staffs' communication style (P = 0.008) was higher than the clients of governmental clinics. In contrast, the satisfaction level of governmental clinics' clients with time-location accessibility (P = 0.010) and financial issues (P = 0.015) was higher than the clients of private clinics. Conclusion: Clients' total satisfaction of private speech therapy clinics was significantly higher than that of governmental clinics of Ahvaz city. Thus, for quantitative and qualitative improvement of governmental clinics, supervisory staff should pay attention to quality of therapeutic services, staffs' communication style and physical environment of clinics. Keywords: Client's satisfaction, Speech therapy, Governmental clinic, Private clinic